From Hostility to Conciliation: Charting Syed Sheikh Al-Hadi’s Attitude towards Colonialism through the Analysis of al-Imam and al-Ikhwan - Mohd Bakhit, Mohamad Tauhid (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
Syed Sheikh al-Hadi (1867–1934) is a central figure in the study of Islamic reformism in the Malay world. To propagate his ideas, he established three journals: al-Imam (1906–1908), al-Ikhwan (1926–1931) and Saudara (1928–1941). Among these, al-Imam has been the most extensively studied, while al-Ikhwan remains significantly overlooked as a primary source for understanding al-Hadi’s thoughts. This neglect disregards critical insights into potential shifts and developments in his ideas, especially since al-Ikhwan was published nearly two decades after al-Imam ceased publication. Specifically, this gap has led to unsatisfactory conclusions regarding al-Hadi’s attitude towards the British colonisers. Without accounting for any shift that had taken place over the decades, several existing studies either depict al-Hadi as fervently and consistently anti-colonial or conclude otherwise, directly contradicting each other. Through a textual analysis of al-Ikhwan and comparison with his earlier writings in al-Imam, this paper argues that a significant shift in his stance towards the colonisers had occurred from hostility in al-Imam to conciliation in al-Ikhwan. Using a socio-historical analysis, it further demonstrates that this shift can be explained by the differing contexts in which al-Hadi was writing for each periodical. This highlights al-Hadi’s critical approach to reform—one that was not merely an imitation of prominent reformists elsewhere, but firmly grounded in the circumstances he faced. Full text: PDF